Synthesis of Mesoporous γ-Alumina Support for Water Composite Sorbents for Low Temperature Sorption Heat Storage - Manca Ocvirk; Alenka Ristić; Nataša Zabukovec Logar (Energies, 2021)
The efficiency of thermochemical heat storage is crucially determined by the performance of the sorbent used, which includes a high sorption capacity and a low regeneration temperature. The thermochemical salt hydrate– γ-alumina composite sorbents are promising materials for this application but lack systematic study of the influence of γ-alumina structural properties on the final storage performance. In this study, mesoporous γ-Al2O3 supports were prepared by solvothermal and hydrothermal synthesis containing a block copolymer (F-127) surfactant to design thermochemical CaCl2 and LiCl composite water sorbents. Altering the solvent in the synthesis has a significant effect on the structural properties of the γ-Al2O3 mesostructure, which was monitored by powder XRD, nitrogen physisorption, and SEM. Solvothermal synthesis led to a formation of mesoporous γ-Al2O3 with higher specific surface area (213 m2/g) and pore volume (0.542 g/cm3) than hydrothermal synthesis (147 m2/g; 0.414 g/cm3). The highest maximal water sorption capacity (2.87 g/g) and heat storage density (5.17 GJ/m3) was determined for W-46-LiCl containing 15 wt% LiCl for space heating, while the best storage performance in the sense of fast kinetics of sorption, without sorption hysteresis, low desorption temperature, very good cycling stability, and energy storage density of 1.26 GJ/m3 was achieved by W-46-CaCl2.